Michael Allen, ed., The New Cambridge Companion to Christian Doctrine (Cambridge: Cambridge University Press, 2023), pp. xiii + 370. ISBN 9781108885959 - McInroy, Mark (Journal of Anglican studies, 2025)
Michael Allen, ed., The New Cambridge Companion to Christian Doctrine (Cambridge: Cambridge University Press, 2023), pp. xiii + 370. ISBN 9781108885959 - Volume 23 Issue 1